Reviewing the etiologic agents, microbe-host relationship, immune response, diagnosis, and treatment in chromoblastomycosis - Passero, Luiz Felipe Domingues [UNESP]; Cavallone, Italo Novais [UNESP]; Belda, Walter (Hindawi, 2021)
Chromoblastomycosis (CBM) is a neglected human disease, caused by different species of pigmented dematiaceous fungi that cause subcutaneous infections. This disease has been considered an occupational disease, occurring among people working in the field of agriculture, particularly in low-income countries. In 1914, the first case of CBM was described in Brazil, and although efforts have been made, few scientific and technological advances have been made in this area. In the field of fungi and host cell relationship, a very reduced number of antigens were characterized, but available data suggest that ectoantigens bind to the cell membrane of host cells and modulate the phagocytic, immunological, and microbicidal responses of immune cells. Furthermore, antigens cleave extracellular proteins in tissues, allowing fungi to spread. On the contrary, if phagocytic cells are able to present antigens in MHC molecules to T lymphocytes in the presence of costimulation and IL-12, a Th1 immune response will develop and a relative control of the disease will be observed. Despite knowledge of the resistance and susceptibility in CBM, up to now, no effective vaccines have been developed. In the field of chemotherapy, most patients are treated with conventional antifungal drugs, such as itraconazole and terbinafine, but these drugs exhibit limitations, considering that not all patients heal cutaneous lesions. Few advances in treatment have been made so far, but one of the most promising ones is based on the use of immunomodulators, such as imiquimod. Data about a standard treatment are missing in the medical literature; part of it is caused by the existence of a diversity of etiologic agents and clinical forms. The present review summarizes the advances made in the field of CBM related to the diversity of pathogenic species, fungi and host cell relationship, antigens, innate and acquired immunity, clinical forms of CBM, chemotherapy, and diagnosis.